Improving Written Communication : Implementation at Industrial Design Engineering - Törlind, Peter (Luleå tekniska universitet, Människa och teknik, 2019)
The purpose of the paper is to present how we have improved the quality of technical writing for students in Industrial Design Engineering at Luleå University of Technology. To achieve this, we have identified a number of courses focusing on verbal and written communication, one course – Product and production design focus on documenting and reporting a technical development work to a client. During the last seven years, the course has continuously been improved, and this paper contains an in-depth review of the course performed during spring 2018. The review was done by discussions in the teaching team, interviews, workshops, analysis of course documentation (course-reviews, course-pm, assessment-scheme etc.). The evolution of the course and how different support systems have been implemented such as peer-reviews, templates, formative feedback and self-assessment has been developed is described in detail. The current course is designed as a stage gate process with four design reviews, in which the student present and receive critique. At each design review, each team produces a short process memo (PM) that is peer-reviewed. Each student conducted three individual peer reviews, as well as group review. With 56 students in the class (spring 2018) over 180 completed peer reviews are performed by the students themselves before they receive formative feedback from the teachers. Self-assessment is also used, first by the team on their own final documentation. Finally, all student performs a personal self-assessment with feedback from their team members. The final assessment of the student is performed by the teachers and the result is similar to the students’ self-assessment. ISBN för värdpublikation: 978-87-7507-459-4